Proinflammatory cytokines increase glial fibrillary acidic protein expression in enteric glia. Issue 2 (14th January 2004) - von Boyen, G B T; Steinkamp, M; Reinshagen, M; Schäfer, K-H; Adler, G; Kirsch, J
Abstract : Background: Enteric glia protect the integrity of the gut, as loss of enteric glial fibrillary acidic protein (GFAP) positive (+) glia leads to a haemorrhagic jejunoileitis. Crohn's disease (CD) and necrotising enterocolitis (NEC) show pathological changes in enteric glia. Therefore, factors controlling GFAP+ enteric glia are of great interest. The aim of the present study was to characterise enteric glia and determine the effect of interleukin 1β (IL-1β), interleukin 4 (IL-4), tumour necrosis factor α (TNF-α), and lipopolysaccharides (LPS) on cultured enteric glia. Methods: Dissected rat colon and cultured enteric glia cells were double labelled with anti-GFAP and anti-S-100 antibodies. For regulatory studies, enteric glia cells were treated with cytokines and LPS. Proliferation was assayed using bromodeoxyuridine (BrdU) and mitosis of enteric glia was blocked by demecolcine. Results: We were able to distinguish GFAP negative (−) from GFAP+ glia subtypes in situ and in primary cultures. Incubation of cells with IL-1β, TNF-α, and LPS led to a significant increase in GFAP+ enteric glia while IL-4 had no effect on GFAP expression. After incubation with IL-1β, total intracellular GFAP of enteric glia cells was increased. Upregulation of GFAP+ enteric glia could also be observed after stimulation with IL-1β on blocking mitosis. BrdU uptake in stimulated enteric glia showed no increased proliferation rate. Conclusions: Two different types of enteric glia based on GFAP expression exist in the gut. Proinflammatory cytokines and LPS cause a dramatic increase in GFAP+ enteric glia. This suggests that cytokines play an important role in controlling GFAP+ enteric glia which might in turn be involved in modulating the integrity of the bowel during inflammation.